Phytochemical prospection and biological activity of Duroia macrophylla (Rubiaceae) - Daiane Martins; Maria T. Fachin-Espinar; Taciane Almeida de Oliveira; Karen C. S. Lima; Rodrigo M. Cavalcanti; Beatriz R. Teles; Cecilia V. Nunez (GarVal Editorial Ltda., 2014)
Context: Duroia macrophylla (Rubiaceae) is endemic from the Amazon Rainforest. Aims: To perform phytochemical profile of Duroia macrophylla extracts and to evaluate them as antioxidant, insecticidal and cytotoxic. Methods: Dichloromethane and methanol extracts of leaves and branches (collected three times) were subjected to phytochemical screening by comparative thin layer chromatography and NMR analyses. The extracts were assayed to antioxidant (DPPH and Fe-phenanthroline, at 10 μg/mL), insecticidal on Sitophilus zeamais (by ingestion of stored grains and contact, both at 10 mg/mL) and toxic activities on Artemia salina (1000 μg/mL). Results: There were found evidences of terpenes, phenolic substances (phenols and flavonoids) and alkaloids, with differences between the vegetal part, collection period and solvent used. Antioxidant evaluations showed three of twelve were active and two were considered moderately active, with a relationship dependently of concentration. All methanol extracts showed the presence of phenolic substances (phenols and flavonoids) but one showed only phenols. For insecticidal activity, there were three most active extracts, two of which showed only presence of terpenes and the other, besides terpenes, phenolic substances (phenols and flavonoids). For Artemia salina toxicity assay, the five most active were all from the 2nd and 3rd collections. Conclusions: The active extracts of D. macrophylla in each test were different. Three methanol extracts showed antioxidant activity; three extracts showed insecticidal activity and the presence of terpenic substances and five extracts presented cytotoxic activity, but it was not possible to correlate it with any specific secondary metabolite.